ORGANIZATIONAL RESILIENCE OF SECONDARY SCHOOLS: A SECOND CONFIRMATORY FACTOR ANALYSIS - Thunphimol Vasayangkura; Boonchan Sisan (International Journal of Industrial Education and Technology, 2025)
This study conducted a confirmatory factor analysis (CFA) of organizational resilience in secondary schools, with findings based on empirical data. The sample for this research consisted of 500 participants, including school directors, deputy directors, and heads of the subject groups from secondary schools, selected through multi-stage random sampling process. The research instrument was a 5-point rating scale questionnaire that underwent content validity verification. The item discrimination indices of the questionnaire ranged from .20 to .80, and the reliability analysis, using Cronbach's alpha coefficient, yielded a value of .92. The statistical method used for data analysis was confirmatory factor analysis (CFA). The study results revealed that organizational resilience in secondary schools comprises four main factors: adaptive capacity, strategic planning, agility, and improvisation. The assessment of the model's goodness-of-fit indices yielded the following results: Chi-Square = .54, RMSEA = .000, GFI = .98, CFI = 1.00, NFI = .99, RMR = .015, RFI = .99, IFI = 1.00, and AGFI = .96, indicating that the model demonstrated congruence with empirical data. The factor loadings of the four main components ranged from .77 to .98, while the factor loadings of the indicators ranged from .38 to .71. The Cronbach's alpha, composite reliability, and average variance extracted values obtained are in the range of .857 – .931, .803 – .924, and .505 – .710, respectively. These values indicated good reliability and acceptable convergent validity. Therefore, developing secondary schools into resilient organizations requires a thorough understanding and integration of key factors influencing organizational resilience to establish internal environments that support personnel and enable effective management of educational resources.
Keywords: Supply Chain Resilience and Risk Management; Resilience and Mental Health; Employee Performance and Leadership